Serum Uric Acid and the Risk of Dementia: A Systematic Review and Meta-Analysis - Zhou, Zhike; Zhong, Shanshan; Liang, Yifan; Zhang, Xiaoqian; Zhang, Rongwei; Kang, Kexin; Qu, Huiling; Xu, Ying; Zhao, Chuansheng; Zhao, Mei (Frontiers in Aging Neuroscience, 2021)
Background: This meta-analysis aimed to evaluate the relationship of serum uric acid (UA) with risk of dementia and its subtypes. Methods: Embase, Pubmed and Web of Science were searched from inception to July 2020. Random-effects models were employed to analyze the standard mean difference (SMD) with corresponding 95% confidence intervals (CI). Results: Twenty-three eligible studies involving 5,575 participants were identified. The overall results showed lower UA levels in dementia relative to non-dementia controls (SMD=-0.32 [-0.64;-0.01] P=0.04). Subgroup analysis of dementia type demonstrated a significant association of UA with Alzheimer’s disease (AD) (SMD=-0.58 [-1.02;-0.15] P=0.009) and Parkinson's disease with dementia (PDD) (SMD=-0.33 [-0.52;-0.14] P=0.001), but not with vascular dementia (VaD). Stratification analysis of UA concentration revealed that the UA quartile 1 2 was negatively correlated with dementia and neurodegenerative subtypes (P<0.05); whereas a positive correlation of UA quartile 4 with dementia was noted (P=0.028). Additionally, meta-regression analysis on confounders showed that not age, body mass index, diabetes mellitus, hypertension and smoking, but only education (P=0.003) exerted an influence of UA in the risk estimate of dementia. Conclusions: Low concentration of UA (< 292 μmol/L or 4.91 mg/dL) is a potential risk factor for AD and PDD, but not for VaD. The mechanism of different UA concentration in dementia needs to be confirmed by further investigation.